If σ 0 ( n ) = 8 , find sum of all possible values of a satisfying a = σ 0 ( 3 n ) .
Notation : σ 0 ( n ) denote the number of positive factors of the integer n (inclusive of 1 and itself).
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
finally a three-liner!
Log in to reply
I'm still working on it...it's a two-liner now ;) I usually write a rough draft first, save it (to make sure it's not lost if I get interrupted), and then I try to streamline it.
The problem is so though that I have no chance to get it down to one line while showing all my work.
If σ 0 ( n ) = 8 ,
then it has to be expressed as p 1 p 2 p 3 , p 1 3 p 2 or p 1 7 .
Scenario 1: n = p 1 p 2 p 3
Case 1: p 1 = 3
Since n = p 1 p 2 p 3
So 3 n = 3 p 1 p 2 p 3 = p 1 2 p 2 p 3 ⟹ 3 × 2 × 2 = 1 2 f a c t o r s
Case 2: p 2 = 3
Since n = p 1 p 2 p 3
So 3 n = 3 p 1 p 2 p 3 = p 2 2 p 1 p 3 ⟹ 3 × 2 × 2 = 1 2 f a c t o r s
Case 3: p 3 = 3
Since n = p 1 p 2 p 3
So 3 n = 3 p 1 p 2 p 3 = p 3 2 p 1 p 2 ⟹ 3 × 2 × 2 = 1 2 f a c t o r s
Case 4: p 1 , 2 , 3 = 3
Since n = p 1 p 2 p 3
So 3 n = 3 p 1 p 2 p 3 ⟹ 2 × 2 × 2 × 2 = 1 6 f a c t o r s
Scenario 2: n = p 1 3 p 2
Case 1: p 1 = 3
Since n = p 1 3 p 2
So 3 n = 3 p 1 3 p 2 = p 1 4 p 2 ⟹ 5 × 2 = 1 0 f a c t o r s
Case 2: p 2 = 3
Since n = p 1 3 p 2
So 3 n = 3 p 1 3 p 2 = p 1 3 p 1 2 ⟹ 4 × 3 = 1 2 f a c t o r s
Case 3: p 1 , 2 = 3
Since n = p 1 3 p 2
3 n = 3 p 1 3 p 2 ⟹ 2 × 4 × 2 = 1 6 f a c t o r s
Scenario 3: n = p 1 7
Case 1: p 1 = 3
Since n = p 1 7
3 n = 3 p 1 7 = p 1 8 ⟹ 9 f a c t o r s
Case 2: p 1 = 3
Since n = p 1 7
3 n = 3 p 1 7 = 3 p 1 7 ⟹ 8 × 2 = 1 6 f a c t o r s
That's all the cases so 1 2 + 1 6 + 1 0 + 9 = 4 7
As you realized, the main consideration is the largest power of 3 that divides n , which determines the value of σ ( 3 n ) .
Problem Loading...
Note Loading...
Set Loading...
If n = 3 m q where 3 ∣ q , then σ 0 ( n ) = σ 0 ( 3 m ) σ 0 ( q ) = ( m + 1 ) σ 0 ( q ) = 8 , so that m + 1 can be 1,2,4 or 8. Now σ 0 ( 3 n ) = σ 0 ( 3 m + 1 ) σ 0 ( q ) = m + 1 8 ( m + 2 ) , which can be 16, 12, 10, or 9. The answer is 4 7